A Description of Psychological Biases on the Currency Market - Danelia, Giorgi (Ekonomika, 2017)
This article concentrates on the theoretical review of the behavior of market participants from the behavioral point of view. The focus is on currency market and its participants; thus, the most relevant behavioral inclinations are described in the article. In finance literature, behaviorism is heavily connected with the understanding rationale of the financial agents, acting on the financial markets, but for us to consider the broader picture, the behavioral aspect might be a very helpful tool for analyzing actions of economic agents on a more global scale. In this article, the main focus is on the currency market and its participants, namely the government and/or central bank as a policy maker and implementer on the one side of the market, and private rationale agents, concentrated purely on commercial return maximization and risk minimization, on the other side. Obviously, the private agents interact with each other and it forms a standard game theory framework, but more interesting is the relationship between the policy maker and the rest of the market, their incentives, perceptions etc., which are described in this article. The article strongly suggests that behavioral analyses should be one of the main pillars for analyses of the general economic environment and for currency crises analyses as well.